A Study of the Influence of Negative Temperatures on the Impact Strength of a Carbon-Fiber Composite with a Hybrid Matrix - Kosenko, E. A.; Baurova, N. I.; Zorin, V. A. (Polymer science. Series D, Glues and sealing materials, 2023)
A technique for creating carbon-fiber composites with a hybrid matrix formed by an epoxy binder and a material that represents an independent liquid phase in the composite structure (anaerobic polymer material, silicone elastomer, synthetic wax) is described. The addition of components of the liquid phase to the composition of the polymer matrix leads to a change in the complex properties of the composite, and the features of the chemical and molecular structure of the materials of the liquid phase contribute to a change in the characteristics of the phase transition. One of the criteria for assessing the properties of composites based on polymer matrices is impact strength. The article presents the results of testing carbon-fiber composites with various types of hybrid matrices (formed by various components of the liquid phase) for impact strength after exposure at temperatures of 20 ± 2 and –30°C. An assessment was made of the influence of the components of the liquid phase on the change in impact strength and loss of impact strength of the composite after exposure to negative temperature conditions. Samples with anaerobic polymer material in the hybrid matrix have the highest average impact strength, while the absence of loss of impact strength after exposure to subzero temperatures is observed in samples with synthetic wax.